Drinking from the river of light : the life of expression - Nepo, Mark (Sounds True, 2019)
“Meaningful art, enduring art<U+2015>and the transformative process it awakens<U+2015>keeps us alive,” writes Mark Nepo. With Drinking from the River of Light, this bestselling poet and philosopher will lead you on a journey to discover just how art and authentic expression can bring our deepest truths to bear in the world. In this collection of interconnected essays and poetry<U+2015>covering subjects ranging from the importance of staying in conversation with other forms of life to a consideration of how innovators such as Matisse, Rodin, and Beethoven saw the world<U+2015>Nepo presents a lyrical ode to the creative urge that stirs in each of us. Whether it<U+2019>s the search for a metaphor to reveal life<U+2019>s beauty or the brushstroke that will thoroughly capture the moment, Drinking from the River of Light examines what it means to go “. . . beyond the boundaries of art, where the viewer and participant are one.”